Enhancing Students' Global Perspective-Taking to Improve Virtual Team Performance: A Swift Trust Theory Perspective - Erskine, Michael A.; Zaza, Sam; Araújo, Rafael D.; Horita, Flávio E. A.; Wahls, Naomi (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Contemporary organizations rely on global virtual teams. This trend, exasperated due to the Covid-19 pandemic, aligns with ongoing globalization and digital transformation efforts. The information system (IS) scholarship has a strong interest in studying groups that develop digital technologies with a frequent focus on global virtual teams. Such teams, which frequently form ad hoc, require a swift formation of trust to be effective. Global-perspective taking overcomes intercultural trust barriers and presents an opportunity for more effective teams. Problem: However, academic IS programs traditionally do not teach or assess concepts such as global-perspective in their students. Our study assesses whether university IS educators can impart global perspective-taking through online intercultural exchanges (OIEs). Theoretical reference: We examine the effects of global perspective-taking (comprising cultural intelligence, global citizenship, and civic-mindedness) on the effectiveness of global virtual teams through the lens of swift trust theory. Method: We conducted an exploratory study by creating OIEs in the context of web development coursework between students in the United States and Brazil (N=131). Results: We found that an OIE environment led to enhanced global perspective-taking and improved student outcomes. The swift trust theory suggests that such outcomes would ultimately enhance virtual team performance. Impact on the IS area: We contribute to the IS scholarship by extending the swift trust theory to include global perspective-taking and provide practical suggestions to academic IS programs on implementing effective OIE practices. We also report the benefits of global perspective-taking on international virtual team performance, which is of interest to hiring organizations.